The impact of a program on the values of citizenship on the readiness of girls in adolescence in Al- Jouf to include in the artistic production - Al-Orjan, Sanaa (Journal of Educational and Psychological Sciences, 2019)
The study aims to identify the impact of the program of citizenship values on the readiness of the girls at adolescence stage in Aljouf area to include them in the artistic products. The study uses the semi- experimental approach where an analysis tool is constructed for the technical works which have four sessions which distributed to four axes which is applied to a sample who are intended to be the girls who are used to go to the neighborhood club. The sample consists of 20 girls. The results show that there are statistically significance differences at the level of ,05 between the mean of the pretest which is (1.34) and the mean of the posttest which is (2.62) in the values of citizenship Which are (love of the homeland, participation, tolerance and preservation of the public property). In the light of the results the researcher states recommendations and suggestions to renforce the citizenship values in Aljouf area and in the kingdom in general.